Electric vehicle modeling: a review - Alzehawi, Ibraheem. S. M.; Faris, Waleed Fekry; Darsivan, Fadly Jashi; Rafeeq, Mohammed (Springer, 2023)
The emission of conventional vehicles nowadays contributes significantly to the escalating pollution issues. However, hybrid systems have more fuel economy than standard automobiles, and the end purpose is to have all-electric automobiles. Nowadays, hybrid electric vehicle systems can be located in various journal arti-cles. However, there are few research papers to offer a detailed technical analysis of pure electric vehicles. The features and common types of energy sources and drive machine for Electric Vehicle is described. The current pure electric vehicle types are then illustrated. In addition, study comprehensively reviews and elaborated different approaches specifically using MATLAB-Simulink tool used for modeling and simulation of electric vehicle to increase performance metrics and build basis for experimental work. The review provides comprehensive understanding of elec-tric vehicle and modelling techniques to address the challenges and issues of electric vehicle.